Eco-Centric Legal Integration for Environmental Monitoring in Nusantara Capital City (NCC) and Putrajaya - Istislam; Anindita Purnama Ningtyas; Mohamad Rifan; Dina Imam Supaat; Amelia Ayu Paramitha (NAJAHA Education Development Center (NEDC), 2026)
Non-Indexed Publication